Decoupling of biological pump strength and efficiency in the eastern equatorial Pacific during the Middle Miocene Climate Optimum - Yilin Liu; Brandon B. Bell; Elizabeth M. Griffith; Mingsong Li; Yi Ge Zhang; Qingqing Jiang; Weiqi Yao (Earth and Planetary Science Letters, 2026)

A theoretical model for local buckling of FRP-confined CFST columns - Yue-Ling Long; Xiang-Hua Yue; Sheng Ge; Leroy Gardner; M. Ahmer Wadee (Engineering Structures, 2026)

Resilience assessment of metro-bus composite networks under sudden disruptions integrating passenger behavior - Yuanwen Lai; Yuchen Ge; Shiqi Zhang; Ming Guan; Said M. Easa; Shuyi Wang (Transportation Research Part D: Transport and Environment, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Leaf Size Variation in Response to Climate Drivers Depends on Plant Life Form - Jiayi Lu; Shihao Wen; Siyu Chen; Yuran Dong; Xiuping Wu; Yao Li; Min Zhang; Zhiwei Ge; Jonathan M. Chase; Lingfeng Mao (Journal of Biogeography, 2026)
Aim Plant leaf size and shape vary across major climatic gradients, reflecting the mechanisms for how plants regulate the balance of carbon, water, and heat. However, the influence of climate on leaf traits can be confounded by multiple factors, and the complex variation among different plant groups remains insufficiently understood. Here, we investigated how climate influences leaf size traits and whether this effect is moderated by plant life form. Location China. Taxon Angiosperms. Methods Based on leaf length, width, and aspect ratio data from 26,726 angiosperm species distributed across major climate gradients in China, we analysed the effects of temperature and precipitation on leaf size traits, and compared differences among plant life forms (woody vs. herbaceous and evergreen vs. deciduous). Additionally, spatial heterogeneity was assessed across eight vegetation zones. Results Leaves are generally larger and rounder in warm and humid areas, and smaller and narrower in cooler and more arid areas. All leaf size traits respond more strongly to precipitation than temperature, with leaf length showing the strongest responses to both climate variables. Herbaceous and deciduous species exhibit stronger climate responses nationwide, whereas woody and evergreen species are more sensitive within vegetation zones. Key responsive traits show clear geographic shifts. Main Conclusions Overall, we find that leaf size and shape vary strongly across China, as a result of climate variation, but these patterns are modified by dominant regional ecological processes and the ecological strategies of plant life forms. These findings not only help clarify variation in plant traits along climatic gradients, but also provide a theoretical framework for predicting how different plant morphologies will respond to ongoing climate change.

Cropping Systems Mediate Carbon and Nitrogen Substrate Effects on Soil Carbon Dioxide and Nitrous Oxide Emissions - Yuan Li; Wenwen Liu; Ying Li; Tida Ge; Tongtong Guan; Dong-Gill Kim; Guopeng Liang; Narasinha Shurpali; Hem Raj Bhattarai; Perttu Virkajärvi; Kadambot H. M. Siddique; Yuying Shen (Journal of Soil Science and Plant Nutrition, 2026)
Agricultural management practices fundamentally influence soil greenhouse gas emissions, yet the mechanisms governing these emissions across different cropping systems remain incompletely understood. This study investigated how carbon (C) substrates and nitrogen (N) additions regulate carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) emissions in soils from contrasting agricultural systems. Using a factorial design, we examined the effects of C substrates (glucose, citric acid, glutamine) and N addition (KNO 3 ) on greenhouse gas emissions from soils under three-year continuous wheat ( Triticum aestivum ) or lucerne ( Medicago sativa ) cultivation. Lucerne soils showed consistently higher N 2 O emissions (0.42 ± 0.04 nmol m –2 s –1 ) compared to wheat soils (0.35 ± 0.03 nmol m –2 s –1 ). CO 2 emissions showed substrate-specific responses, with glutamine treatment yielding the highest emissions (1.35 ± 0.12 µmol m –2 s –1 ), followed by citric acid (1.12 ± 0.09 µmol m –2 s –1 ) and glucose (0.98 ± 0.08 µmol m –2 s –1 ), all significantly exceeding the water control (0.82 ± 0.07 µmol m –2 s –1 ). Structural equation modeling revealed that substrate effects were mediated through distinct pathways in each system, with iron availability and enzyme activities explaining 37% and 29% of emission variations in lucerne and wheat soils, respectively. Network analysis suggested strong correlations between N 2 O emissions and soil iron fractions ( r = 0.64–0.69) in both systems. Citric acid enhanced N 2 O emissions by 31% through pH-mediated effects on denitrification, while glucose and glutamine suppressed emissions by 24% and 18%, respectively, through enhanced N immobilization. The contrasting responses between systems reflected fundamental differences in microbial resource utilization strategies, with lucerne soils showing stronger coupling between C and N cycling processes (path coefficient = 0.45). These findings suggest that greenhouse gas mitigation strategies should consider both cropping system legacy effects and substrate-specific response patterns. System-specific approaches targeting both C input quality and N availability may offer effective pathways for emission reduction in agricultural soils.

Influences of Structural and Species Diversity on Forest Resistance to Drought - Erin T. H. Crockett; Qinfeng Guo; Jeff W. Atkins; Ge Sun; Kevin M. Potter; Jennifer K. Costanza; Scott V. Ollinger; Christopher W. Woodall; Steven McNulty; Carl Trettin; Justin Holgerson; Jingfeng Xiao (Ecology Letters, 2026)
Biodiversity can enhance forest resistance to drought, but the forms of diversity involved and conditions under which diversity confers resistance remain unclear. We used Forest Inventory and Analysis (FIA) plot data to examine whether four variables—structural richness (variation in tree heights, stand density, canopy cover and/or spatial heterogeneity), species richness (number of tree species), structural evenness and species evenness—are associated with the resistance of net primary productivity to drought and whether these relationships change with drought severity and by ecoregion. Structural richness was positively associated and species evenness was negatively associated with resistance, but the strength of these relationships varied by ecoregion. Relationships between structural richness and resistance and between species evenness and resistance became stronger under more severe droughts, supporting the stress gradient hypothesis. Forest managers cannot readily change abiotic conditions but could increase structural richness and select certain species to enhance forest resistance to drought.

Duxseal boundary effects on static and dynamic responses in numerical models validated against small-amplitude dynamic centrifuge tests - Ge Cui; Alec M. Marshall; Charles M. Heron; Liyao Wan (Soil Dynamics and Earthquake Engineering, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

Radiofrequency electromagnetic heating enhanced vitrification of viable large cartilage tissues - Haiyang Ma; Josh Wewerk; Ge Pan; A.J. Riffe; Peng Chen; Yaqian Sun; John M. Alford; Kristi Helke; Girish Srinivas; Hai Yao; David P. Eisenberg; Shangping Wang (Cryobiology, 2025)

Particle-scale design of lithium-ion battery cathodes for manufacture by coupling physics-based modelling with machine learning interpretation - Ruihuan Ge; Mona Faraji Niri; Adam M. Boyce; Robert Heymer; James Marco; Paul R. Shearing; Denis J. Cumming; Rachel M. Smith (Chemical Engineering Journal, 2025)

Impact of sodium intake on blood pressure, mortality and major cardiovascular events: an umbrella review of systematic reviews and meta-analyses - Qiuyu Yang; Robin W. M. Vernooij; Hongfei Zhu; Gihad Nesrallah; Chunyang Bai; Qi Wang; Ying Li; Danni Xia; Małgorzata M. Bała; Sylwia Warzecha; Mingyao Sun; Ahmad Jayedi; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Sustainable production of C6 phenols from lignin via sequential CO and CC bond cleavage over Ni-MgO/hydroxyapatite catalyst - Shitong Yu; Zhitong Ge; Haowei Huang; Julian A. Steele; Francis Kemausuor; Emad M. Hafez; Obid Tursunov; Zhicheng Luo (Chemical Engineering Journal, 2025)

Interactive effects of air pollutants and viral exposure on daily influenza hospital visits in Mongolia - Yihui Ge; Yan Lin; Oyu Tsogtbayar; Ser-Od Khuyagaa; Eelin Khurelbaatar; Jargalsaikhan Galsuren; Lauren Prox; Shiyu Zhang; Robert M. Tighe; Gregory C. Gray; Junfeng Zhang; Daramragchaa Ulziimaa; et al. (Environmental Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial and anchoring effects of zirconia-doped 3D scaffolds for stable zinc anodes - Jinqiu Ye; Tiancheng Ge; Xin Qu; Mohamedazeem M. Mohideen; Ce Wang; Ping Hu; Yong Liu (Chemical Engineering Journal, 2025)

Devising optimized maize nitrogen stress indices in complex field conditions from UAV hyperspectral imagery - Jiating Li; Yufeng Ge; Laila A. Puntel; Derek M. Heeren; Geng Bai; Guillermo R. Balboa; John A. Gamon; Timothy J. Arkebauer; Yeyin Shi (Precision Agriculture, 2025)
Nitrogen Sufficiency Index (NSI) is an important nitrogen (N) stress indicator for precision N management. It is usually calculated using variables such as leaf chlorophyll meter readings (SPAD) and vegetation indices (VIs). However, no consensus has been reached on the most preferred variable. Additionally, conventional NSI (NSI uni ) calculation assumes N being the sole yield-limiting factor, neglecting other factors such as soil water variability. To tackle these issues, this study compared various variables for NSI calculation and evaluated two new N stress indicators in minimizing the impact of confounding water treatment. The following ground- and aerial-derived variables were compared for NSI uni calculation: SPAD, sampled leaf and canopy N content (LNC, CNC), LNC and CNC estimated using hyperspectral images acquired by an Unmanned Aerial Vehicle, and three VIs (Normalized Difference Vegetation Index (NDVI), Normalized Red Edge Index (NDRE), and Chlorophyll Index) from the hyperspectral images. Results demonstrated that ground-measured variables outperformed aerial-based variables in deriving N-responsive NSI. Especially, LNC derived NSI uni responded to N treatment significantly in ten out of thirteen site-date datasets. For the second objective, a modified NSI (NSI w ) and the NDRE/NDVI ratio were compared to NSI uni . NSI w reduced water treatment effects in over 80% of the datasets where NSI uni showed evident impacts. NDRE/NDVI performed similarly to NSI w , with the notable advantage of not requiring prior knowledge of soil water spatial distribution. This research pioneers the optimization of N stress indicators by identifying the best variables for NSI and mitigating the effects of soil water variability. These advancements significantly contribute to precision N management in complex field conditions.

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Proteomics Reveals Divergent Cardiac Inflammatory and Metabolic Responses After Inhalation of Ambient Particulate Matter With or Without Ozone - Yue Ge; Maliha S. Nash; Witold M. Winnik; Maribel Bruno; William T. Padgett; Rachel D. Grindstaff; Mehdi S. Hazari; Aimen K. Farraj (Cardiovascular Toxicology, 2024)

Extended Bouc-Wen model identification using shaking table test data of ageing RC bridge piers - Xiao Ge; Yan-Hui Liu; Yu-Qing Yang; Nicholas A. Alexander; Mohammad M. Kashani (Bulletin of Earthquake Engineering, 2024)

Do Experimental Forests and Ranges of the Southeastern United States Represent the Climate, Ecosystem Structure, and Ecosystem Functions of the Region? - Jingfeng Xiao; Ge Sun; Kevin M Potter; Johnny Boggs; Qingyuan Zhang; Steven G McNulty (Journal of Forestry, 2024)
There are twenty experimental forest and range sites (EFRs) across the southeastern United States that are currently maintained by the USDA Forest Service (Forest Service) to conduct forest ecosystem research for addressing ecosystem management challenges. The overall objective of this study was to use multiple gridded datasets to assess the extent to which the twenty EFRs represent the climate, ecosystem structure, and ecosystem functions of southeastern forests. The EFRs represent the large variability of climate conditions across the region relatively well, but we identified small representation gaps. The representativeness of ecosystem structure by these EFRs can be improved by establishing EFRs in forests with relatively low tree cover, leaf area index, or tree canopy height. The current EFRs also represent the forest ecosystem functions of the region relatively well, although areas with intermediate and low aboveground biomass and water yield are not well represented. The trends in climate, ecosystem structure, and ecosystem functions were generally consistent between the region and the EFRs. Our study indicates that the current EFRs represent the region relatively well, but establishing additional EFRs in specific areas within the region could help more completely assess how southeastern forests respond to climate change, disturbance, and management practices. Study Implications: This study across the experimental forests and ranges (EFRs) and the southeastern forest region fills the knowledge gap regarding climate, ecosystem structure, and ecosystem functions of EFRs in the context of the broader southeastern forest region. Understanding ecosystem functions and structures across the EFR network can help the Southern Research Station to address new research questions. Our study indicates that the current EFRs represent the climate, ecosystem structure, and ecosystem functions of southeastern forests well. However, establishing additional EFRs in certain regions could help more completely assess how southeastern forests respond to climate change, disturbance, and management practices.

3D mineral prospectivity modeling using multi-scale 3D convolution neural network and spatial attention approaches - Xiaohui Li; Yuheng Chen; Feng Yuan; Simon M. Jowitt; Mingming Zhang; Can Ge; Zhiqiang Wang; Yufeng Deng (Geochemistry, 2024)

P10-07 Polystyrene micro – and nanoplastics induced spermatogenesis disorder via disturbance of mitochondrial dynamics in mice - M. Zhao; J. Xie; J. Zhang; B. Zhao; Y. Zhang; J. Xue; R. Zhang; R. Zhang; H. Wang; Y. Li; W. Ge; X. Zhou (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Development of an agroinfiltration-based transient hairpin RNA expression system in pak choi leaves (Brassica rapa ssp. chinensis) for RNA interference against Liriomyza sativae - Shu-Peng Li; Zi-Xu Chen; Ge Gao; Ya-Qi Bao; Wen-Ying Fang; Ya-Nan Zhang; Wan-Xue Liu; Marcé Lorenzen; Brian M. Wiegmann; Jing-Li Xuan (Pesticide Biochemistry and Physiology, 2024)

Bioenergetic and Metabolic Profiling of a Triple Negative Breast Cancer Cell Line and its High Invasive Isogenic Subtype - Ziqian Ge; Martina Wallace; Mary F. Rooney; Karsten Hokamp; Fiona M. Roche; Susan McDonnell; Richard K. Porter (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

α-Lactalbumin: Functional properties and potential health benefits - Xinyu Ge; Jie Zhang; Joe M. Regenstein; Dasong Liu; Yinbo Huang; Yongsheng Qiao; Peng Zhou (Food Bioscience, 2024)

Biomass-MOF composites in wastewater treatment, air purification, and electromagnetic radiation adsorption – A review - Jinxuan Jiang; Yang Shi; Mingjun Wu; Mashallah Rezakazemi; Tejraj M. Aminabhavi; Runzhou Huang; Chong Jia; Shengbo Ge (Chemical Engineering Journal, 2024)

CometChip enables parallel analysis of multiple DNA repair activities [DNA repair 106 (2021) 103176–103202] - Jing Ge; Le P. Ngo; Simran Kaushal; Ian J. Tay; Elina Thadhani; Jennifer E. Kay; Patrizia Mazzucato; Danielle Chow; Jessica Fessler; David M. Weingeist; Robert W. Sobol; Leona D. Samson; et al. (DNA Repair, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Global wild rice germplasm resources conservation alliance: World Wild-Rice Wiring - Xiaoming Zheng; Disna Ratnasekera; Jiayu Fan; Robert J. Henry; Beng-Kah Song; Kenneth M. Olsen; Bal Krishna Joshi; Maria Celeste N. Banaticla-Hilario; Tonapha Pusadee; Adane Getachew Melaku; Yêyinou Laura Estelle Loko; Koukham Vilayheuang; et al. (Molecular Plant, 2024)

Enhanced combustion of toluene on bimetallic-organic frameworks Fe-doped Mn2O3 nanoparticles - Yi Yu; Fanfan Li; Shengbo Ge; Xingchuan Yang; Mashallah Rezakazemi; Shuangquan Zang; Tejraj M. Aminabhavi; Li Xu (Chemical Engineering Journal, 2024)

Assessing the performance of winged caisson foundations for offshore wind turbines - Koohyar Faizi; Asaad Faramarzi; Samir Dirar; David Chapman; Ge Cui; Charles M. Heron; Alec M. Marshall (Marine Georesources & Geotechnology, 2024)

Plant-mediated CH4 exchange in wetlands: A review of mechanisms and measurement methods with implications for modelling - Mengyu Ge; Aino Korrensalo; Raija Laiho; Lukas Kohl; Annalea Lohila; Mari Pihlatie; Xuefei Li; Anna M. Laine; Jani Anttila; Anuliina Putkinen; Weifeng Wang; Markku Koskinen (Science of The Total Environment, 2024)

A review on recent advances in the applications of composite Fe 3 O 4 magnetic nanoparticles in the food industry - Lina Dong; Ge Chen; Guangyang Liu; Xiaodong Huang; XiaoMin Xu; Lingyun Li; Yanguo Zhang; Jing Wang; Maojun Jin; Donghui Xu; A. M. Abd El-Aty (Critical Reviews in Food Science and Nutrition, 2024)

Amine-functionalized UiO-66 incorporated electrospun cellulose/chitosan porous nanofibrous membranes for removing copper ions - Ronggang Luo; Kaixing Zhang; Yongjian Qin; Linkun Xie; Xijuan Chai; Lianpeng Zhang; Guanben Du; Shengbo Ge; Mashallah Rezakazemi; Tejraj M. Aminabhavi; Kaimeng Xu (Chemical Engineering Journal, 2024)

Shift in algal blooms from micro‐ to macroalgae around China with increasing eutrophication and climate change - Yuan Feng; Yonglong Xiong; Jason M. Hall‐Spencer; Kailin Liu; John Beardall; Kunshan Gao; Jingke Ge; Juntian Xu; Guang Gao (Global Change Biology, 2024)
Blooms of microalgal red tides and macroalgae (e.g., green and golden tides caused by Ulva and Sargassum ) have caused widespread problems around China in recent years, but there is uncertainty around what triggers these blooms and how they interact. Here, we use 30 years of monitoring data to help answer these questions, focusing on the four main species of microalgae Prorocentrum donghaiense , Karenia mikimotoi , Noctiluca scintillans , and Skeletonema costatum ) associated with red tides in the region. The frequency of red tides increased from 1991 to 2003 and then decreased until 2020, with S. costatum red tides exhibiting the highest rate of decrease. Green tides started to occur around China in 1999 and the frequency of green tides has since been on the increase. Golden tides were first reported to occur around China in 2012. The frequency of macroalgal blooms has a negative linear relationship with the frequency and coverage of red tides around China, and a positive correlation with total nitrogen and phosphorus loads as well as with atmospheric CO 2 and sea surface temperature (SST). Increased outbreaks of macroalgal blooms are very likely due to worsening levels of eutrophication, combined with rising CO 2 and SST, which contribute to the reduced frequency of red tides. The increasing grazing rate of microzooplankton also results in the decline in areas affected by red tides. This study shows a clear shift of algal blooms from microalgae to macroalgae around China over the past 30 years driven by the combination of eutrophication, climate change, and grazing stress, indicating a fundamental change in coastal systems in the region.

Using Ribonucleoprotein-based CRISPR/Cas9 to Edit Single Nucleotide on Human Induced Pluripotent Stem Cells to Model Type 3 Long QT Syndrome (SCN5A±) - Ning Ge; Min Liu; Rui Li; Nicholas M. Allen; Joseph Galvin; Sanbing Shen; Timothy O’Brien; Terence W. Prendiville (Stem Cell Reviews and Reports, 2023)
Human induced pluripotent stem cells (hiPSCs) have been widely used in cardiac disease modelling, drug discovery, and regenerative medicine as they can be differentiated into patient-specific cardiomyocytes. Long QT syndrome type 3 (LQT3) is one of the more malignant congenital long QT syndrome (LQTS) variants with an SCN5A gain-of-function effect on the gated sodium channel. Moreover, the predominant pathogenic variants in LQTS genes are single nucleotide substitutions (missense) and small insertion/deletions (INDEL). CRISPR/Cas9 genome editing has been utilised to create isogenic hiPSCs to control for an identical genetic background and to isolate the pathogenicity of a single nucleotide change. In this study, we described an optimized and rapid protocol to introduce a heterozygous LQT3-specific variant into healthy control hiPSCs using ribonucleoprotein (RNP) and single-stranded oligonucleotide (ssODN). Based on this protocol, we successfully screened hiPSCs carrying a heterozygous LQT3 pathogenic variant ( SCN5A ± ) with high efficiency (6 out of 69) and confirmed no off-target effect, normal karyotype, high alkaline phosphatase activity, unaffected pluripotency, and in vitro embryonic body formation capacity within 2 weeks. In addition, we also provide protocols to robustly differentiate hiPSCs into cardiomyocytes and evaluate the electrophysiological characteristics using Multi-electrode Array. This protocol is also applicable to introduce and/or correct other disease-specific variants into hiPSCs for future pharmacological screening and gene therapeutic development. Graphical Abstract

Structural and species diversity explain aboveground carbon storage in forests across the United States: Evidence from GEDI and forest inventory data - Erin T.H. Crockett; Jeff W. Atkins; Qinfeng Guo; Ge Sun; Kevin M. Potter; Scott Ollinger; Carlos A. Silva; Hao Tang; Christopher W. Woodall; Justin Holgerson; Jingfeng Xiao (Remote Sensing of Environment, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Discrete element method and electrochemical modelling of lithium ion cathode structures characterised by X-ray computed tomography - Ruihuan Ge; Adam M. Boyce; Ye Shui Zhang; Paul R. Shearing; Denis J. Cumming; Rachel M. Smith (Chemical Engineering Journal, 2023)

Ancient DNA reveals potentially toxic cyanobacteria increasing with climate change - Jifeng Zhang; Kun Shi; Hans W. Paerl; Kathleen M. Rühland; Yanli Yuan; Rong Wang; Jie Chen; Mengjuan Ge; Lingling Zheng; Zhiping Zhang; Boqiang Qin; Jianbao Liu; et al. (Water Research, 2023)

Multiple-functionalized biochar affects rice yield and quality via regulating arsenic and lead redistribution and bacterial community structure in soils under different hydrological conditions - Xing Yang; Zhinan Dai; Chengjun Ge; Huamei Yu; Nanthi Bolan; Daniel C.W. Tsang; Hocheol Song; Deyi Hou; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Iron-modified phosphorus- and silicon-based biochars exhibited various influences on arsenic, cadmium, and lead accumulation in rice and enzyme activities in a paddy soil - Xing Yang; Ergang Wen; Chengjun Ge; Ali El-Naggar; Huamei Yu; Shengsen Wang; Eilhann E. Kwon; Hocheol Song; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Plant Growth Stimulating Bacteria and Filter Mud Cake Enhance Soil Quality and Productivity of Mango (Mangifera indica L.) - Yu Ge; Arwa Abdulkreem AL-Huqail; Zhaoxi Zhou; Esmat F. Ali; Adel M. Ghoneim; Mamdouh Eissa; Mahmoud S. El-Sharkawy; Zheli Ding (Journal of Soil Science and Plant Nutrition, 2022)

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

The resource recovery potential of blackwater and foodwaste: anaerobic co-digestion in serial semi-continuous stirred tank reactors - A. S. Giwa; A. G. Memon; M. Vakili; Y. Ge; B. Wang (International Journal of Environmental Science and Technology, 2022)

Peripartum cardiomyopathy: a global effort to find the cause and cure for the rare and little understood disease - Amy Li; K. Campbell; S. Lal; Y. Ge; A. Keogh; P. S. Macdonald; P. Lau; John Lai; W. A. Linke; J. Van der Velden; A. Field; B. Martinac; et al. (Biophysical Reviews, 2022)
In this review, we present our current understanding of peripartum cardiomyopathy (PPCM) based on reports of the incidence, diagnosis and current treatment options. We summarise opinions on whether PPCM is triggered by vascular and/or hormonal causes and examine the influence of comorbidities such as preeclampsia. Two articles published in 2021 strongly support the hypothesis that PPCM may be a familial disease. Using large cohorts of PPCM patients, they summarised the available genomic DNA sequence data that are expressed in human cardiomyocytes. While PPCM is considered a disease predominately affecting the left ventricle, there are data to suggest that some cases also involve right ventricular failure. Finally, we conclude that there is sufficient evidence to warrant an RNAseq investigation and that this would be most informative if performed at the cardiomyocytes level rather than analysing genomic DNA from the peripheral circulation. Given the rarity of PPCM, the combined resources of international human heart tissue biobanks have assembled 30 ventricular tissue samples from PPCM patients, and we are actively seeking to enlarge this patient base by collaborating with human heart tissue banks and research laboratories who would like to join this endeavour.

Phenylpropanoid conjugated iridoids with anti-malarial activity from the leaves of Morinda morindoides - Yasinjan Hashim; Kazufumi Toume; Shusaku Mizukami; Yue-Wei Ge; Mayumi Taniguchi; Awet Alem Teklemichael; Nguyen Tien Huy; Joseph M. Bodi; Kenji Hirayama; Katsuko Komatsu (Journal of Natural Medicines, 2021)

Effects of different types of land-use on taxonomic and functional diversity of benthic macroinvertebrates in a subtropical river network - Zhenyuan Liu; Zhengfei Li; Diego M. P. Castro; Xiang Tan; Xiaoming Jiang; Xingliang Meng; Yihao Ge; Zhicai Xie (Environmental Science and Pollution Research, 2021)

Effects of Dual Fronts on the Spatial Pattern of Chlorophyll-a Concentrations in and off the Changjiang River Estuary - Weiqi Li; Jianzhong Ge; Pingxing Ding; Jianfei Ma; Patricia M. Glibert; Dongyan Liu (Estuaries and Coasts, 2021)

Risk assessment of the step-by-step return-to-work policy in Beijing following the COVID-19 epidemic peak - Wen-bin Zhang; Yong Ge; Mengxiao Liu; Peter M. Atkinson; Jinfeng Wang; Xining Zhang; Zhaoxing Tian (Stochastic Environmental Research and Risk Assessment, 2021)

Small strain moduli of compacted silt by ultrasonic pulse velocity measurements - David M. Weidinger; Honghua Zhao; Annie On-Lei Kwok; Xin Kang; Louis Ge (Marine Georesources & Geotechnology, 2020)

Differences in soil water changes and canopy temperature under varying water × nitrogen sufficiency for maize - Tsz Him Lo; Daran R. Rudnick; Kendall C. DeJonge; Geng Bai; Hope Njuki Nakabuye; Abia Katimbo; Yufeng Ge; Trenton E. Franz; Xin Qiao; Derek M. Heeren (Irrigation Science, 2020)

Estimating the burden of lung cancer in Canada attributed to occupational radon exposure using a novel exposure assessment method - C. B. Ge; J. Kim; F. Labrèche; E. Heer; C. Song; V. H. Arrandale; M. Pahwa; C. E. Peters; P. A. Demers (International Archives of Occupational and Environmental Health, 2020)
Objective Exposure to radon causes lung cancer. The scope and impact of exposure among Canadian workers have not been assessed. Our study estimated occupational radon exposure in Canada and its associated lung cancer burden. Methods Exposed workers were identified among the working population during the risk exposure period (1961–2001) using data from the Canadian Census and Labour Force Survey. Exposure levels were assigned based on 12,865 workplace radon measurements for indoor workers and assumed to be 1800 mg/m 3 for underground workers. Lung cancer risks were calculated using the Biological Effects of Ionizing Radiation (BEIR) VI exposure-age-concentration model. Population attributable fractions were calculated with Levin’s equation and applied to 2011 Canadian lung cancer statistics. Results Approximately 15.5 million Canadian workers were exposed to radon during the risk exposure period. 79% of exposed workers were exposed to radon levels < 50 Bq/m 3 and 4.8% were exposed to levels > 150 Bq/m 3 . We estimated that 0.8% of lung cancers in Canada were attributable to occupational radon exposure, corresponding to approximately 188 incident lung cancers in 2011. Conclusions The lung cancer burden associated with occupational radon exposure in Canada is small, with the greatest burden occurring among those exposed to low levels of radon.

Overexpression of ferulate 5-hydroxylase increases syringyl units in Sorghum bicolor - Hannah M. Tetreault; Tammy Gries; Nathan A. Palmer; Deanna L. Funnell-Harris; Shirley Sato; Zhengxiang Ge; Gautam Sarath; Scott E. Sattler (Plant Molecular Biology, 2020)

Microbial, Physical, and Chemical Changes in Galveston Bay Following an Extreme Flooding Event, Hurricane Harvey - Jamie L. Steichen; Jessica M. Labonté; Rachel Windham; David Hala; Karl Kaiser; Samantha Setta; Patricia C. Faulkner; Hernando Bacosa; Ge Yan; Manoj Kamalanathan; Antonietta Quigg (Frontiers in Marine Science, 2020)

Hurricanes Accelerate Dissolved Organic Carbon Cycling in Coastal Ecosystems - Ge Yan; Jessica M. Labonté; Antonietta Quigg; Karl Kaiser (Frontiers in Marine Science, 2020)

Nonlinear dynamic behaviour of severely corroded reinforced concrete columns: shaking table study - Xiao Ge; Matthew S. Dietz; Nicholas A. Alexander; Mohammad M. Kashani (Bulletin of Earthquake Engineering, 2020)
A set of benchmark, medium scale, shaking table tests on corroded reinforced concrete (RC) columns is conducted with the aim of investigating the effects of corrosion damage on the nonlinear dynamic behaviour of RC bridge piers. The experimental programme consists of an uncorroded control specimen and two corroded RC column specimens, with identical structural details. An accelerated corrosion procedure is used to corrode the RC columns. The uncorroded and corroded specimens are subjected to far-field long duration ground motion excitations. The two corroded columns had 51% and 65% average mass loss ratios. The testing sequence includes slight, extensive, and complete damage levels, followed by an aftershock to examine the cascade effect on the nonlinear dynamic response of the proposed RC columns. The experimental results show that corrosion changes the failure mode of the RC columns, and has a significant negative impact on the residual strength (about 50% mass loss results in about 80% strength reduction) and drift capacity of RC columns.

Burden of non-melanoma skin cancer attributable to occupational sun exposure in Canada - Cheryl E. Peters; J. Kim; C. Song; E. Heer; V. H. Arrandale; M. Pahwa; F. Labrèche; C. B. McLeod; H. W. Davies; C. B. Ge; P. A. Demers (International Archives of Occupational and Environmental Health, 2019)

Significance of non-stationary characteristics of ground-motion on structural damage: shaking table study - Mohammad M. Kashani; Xiao Ge; Matthew S. Dietz; Adam J. Crewe; Nicholas A. Alexander (Bulletin of Earthquake Engineering, 2019)

Deposit characteristics of the Jiweishan rapid long-runout landslide based on field investigation and numerical modeling - Yunfeng Ge; Huiming Tang; M. A. M. Ez Eldin; Hongzhi Chen; Peng Zhong; Li Zhang; Ke Fang (Bulletin of Engineering Geology and the Environment, 2019)

The relationships between seedling root screens, root growth in the field and grain yield for wheat - C. Bai; Y. Ge; R. W. Ashton; J. Evans; A. Milne; M. J. Hawkesford; W. R. Whalley; M. A. J. Parry; J. Melichar; D. Feuerhelm; P. Bansept Basler; M. Bartsch (Plant and Soil, 2019)

Functional trait trade‐off and species abundance: insights from a multi‐decadal study - Xing‐Yue M. Ge; Joshua P. Scholl; Ursula Basinger; Travis E. Huxman; D. Lawrence Venable (Ecology Letters, 2019)
Phylogenetically informed trait comparisons across entire communities show promise in advancing community ecology. We use this approach to better understand the composition of a community of winter annual plants with multiple decades of monitoring and detailed morphological, phenological and physiological measurements. Previous research on this system revealed a physiological trade‐off among dominant species that accurately predicts population and community dynamics. Here we expanded our investigation to 51 species, representing 96% of individual plants recorded over 30 years, and analysed trait relationships in the context of species abundance and phylogenetic relationships. We found that the functional‐trait trade‐off scales to the entire community, albeit with diminished strength. It is strongest for dominant species and weakens as progressively rarer species are included. The trade‐off has been consistently expressed over three decades of environmental change despite some turnover in the identity of dominant species.

Iron‐ and aluminium‐induced depletion of molybdenum in acidic environments impedes the nitrogen cycle - Xiaoxuan Ge; Brian J. Vaccaro; Michael P. Thorgersen; Farris L. Poole; Erica L. Majumder; Grant M. Zane; Kara B. De León; W. Andrew Lancaster; Ji Won Moon; Charles J. Paradis; Frederick von Netzer; David A. Stahl; et al. (Environmental Microbiology, 2019)
Summary Anthropogenic nitrate contamination is a serious problem in many natural environments. Nitrate removal by microbial action is dependent on the metal molybdenum (Mo), which is required by nitrate reductase for denitrification and dissimilatory nitrate reduction to ammonium. The soluble form of Mo, molybdate (MoO 4 2− ), is incorporated into and adsorbed by iron (Fe) and aluminium (Al) (oxy) hydroxide minerals. Herein we used Oak Ridge Reservation (ORR) as a model nitrate‐contaminated acidic environment to investigate whether the formation of Fe‐ and Al‐precipitates could impede microbial nitrate removal by depleting Mo. We demonstrate that Fe and Al mineral formation that occurs as the pH of acidic synthetic groundwater is increased, decreases soluble Mo to low picomolar concentrations, a process proposed to mimic environmental diffusion of acidic contaminated groundwater. Analysis of ORR sediments revealed recalcitrant Mo in the contaminated core that co‐occurred with Fe and Al, consistent with Mo scavenging by Fe/Al precipitates. Nitrate removal by ORR isolate Pseudomonas fluorescens N2A2 is virtually abolished by Fe/Al precipitate‐induced Mo depletion. The depletion of naturally occurring Mo in nitrate‐ and Fe/Al‐contaminated acidic environments like ORR or acid mine drainage sites has the potential to impede microbial‐based nitrate reduction thereby extending the duration of nitrate in the environment.

Sensitive and Selective Detection of Antibiotic D-Penicillamine Based on a Dual-Mode Probe of Fluorescent Carbon Dots and Gold Nanoparticles - Hongwei Ge; Kui Zhang; Huan Yu; Ji Yue; Long Yu; Xinfeng Chen; Tianxin Hou; Khalid A. Alamry; Hadi M. Marwani; Suhua Wang (Journal of Fluorescence, 2018)

Novel characterization method of impedance cardiography signals using time-frequency distributions - Jesús Escrivá Muñoz; Y. Pan; S. Ge; E. W. Jensen; M. Vallverdú (Medical & Biological Engineering & Computing, 2018)

Recent Applications of Mineral Magnetic Methods in Sediment Pollution Studies: a Review - Weiguo Zhang; Chenyin Dong; Simon M. Hutchinson; Can Ge; Feng Wang; Huan Feng (Current Pollution Reports, 2018)

On the role of sphericity of falling rock clusters—insights from experimental and numerical investigations - Ge Gao; M. A. Meguid (Landslides, 2018)

Molecular and phenotypic characterization of transgenic wheat and sorghum events expressing the barley alanine aminotransferase - Pamela A. Peña; Truyen Quach; Shirley Sato; Zhengxiang Ge; Natalya Nersesian; Ismail M. Dweikat; Madhavan Soundararajan; Tom Clemente (Planta, 2017)

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Tectono-stratigraphic evolution and hydrocarbon exploration in the Eocene Southern Lufeng Depression, Pearl River Mouth Basin, South China Sea - J. W. Ge; X. M. Zhu; X. T. Zhang; B. G. Jones; F. S. Yu; Z. C. Niu; M. Li (Australian Journal of Earth Sciences, 2017)

Impact of air pollution induced climate change on water availability and ecosystem productivity in the conterminous United States - Kai Duan; Ge Sun; Yang Zhang; Khairunnisa Yahya; Kai Wang; James M. Madden; Peter V. Caldwell; Erika C. Cohen; Steven G. McNulty (Climatic Change, 2017)

Spectroscopic and biological activity studies of the chromium-binding peptide EEEEGDD - Hirohumi Arakawa; Machender R. Kandadi; Evgeniy Panzhinskiy; Kenneth Belmore; Ge Deng; Ebony Love; Preshus M. Robertson; Juliette J. Commodore; Carolyn J. Cassady; Sreejayan Nair; John B. Vincent (JBIC Journal of Biological Inorganic Chemistry, 2016)

Evolution of the East China Sea sedimentary environment in the past 14 kyr: Insights from tetraethers-based proxies - HuangMin Ge; ChuanLun Zhang; Gerard J. M. Versteegh; LingLing Chen; DaiDu Fan; Liang Dong; JingJing Liu (Science China Earth Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Sorption of Atrazine, 17α-Estradiol, and Phenanthrene on Wheat Straw and Peanut Shell Biochars - Jiangmin Zhou; Hualin Chen; Weilin Huang; Joselito M. Arocena; Shimei Ge (Water, Air, & Soil Pollution, 2016)

Trivalent Chromium has no Effect on Delaying Azoxymethane-Induced Colorectal Cancer in FVB/NJ Mice - Pandora E. White; Ge Deng; M. Kaitlyn Kuykendall; Abbey M. Tadros; Samantha L. Dyroff; Rachel E. Honan; Preshus M. Robertson; John B. Vincent; Jane F. Rasco (Biological Trace Element Research, 2015)

Microbes in beach sands: integrating environment, ecology and public health - Richard L. Whitman; Valerie J. Harwood; Thomas A. Edge; Meredith B. Nevers; Muruleedhara Byappanahalli; Kannappan Vijayavel; João Brandão; Michael J. Sadowsky; Elizabeth Wheeler Alm; Allan Crowe; Donna Ferguson; Zhongfu Ge; et al. (Reviews in Environmental Science and Bio/Technology, 2014)

Patient-specific finite element modeling of the Cardiokinetix Parachute® device: effects on left ventricular wall stress and function - Lik Chuan Lee; Liang Ge; Zhihong Zhang; Matthew Pease; Serjan D. Nikolic; Rakesh Mishra; Mark B. Ratcliffe; Julius M. Guccione (Medical & Biological Engineering & Computing, 2014)

Comparative genotype reactions to Sclerotinia sclerotiorum within breeding populations of Brassica napus and B. juncea from India and China - M. J. Barbetti; S. K. Banga; T. D. Fu; Y. C. Li; D. Singh; S. Y. Liu; X. T. Ge; S. S. Banga (Euphytica, 2014)

Towards a high‐resolution climatography of seasonal precipitation over Israel - D. Rostkier‐Edelstein; Y. Liu; W. Wu; P. Kunin; A. Givati; M. Ge (International Journal of Climatology, 2014)
This study demonstrates the capability of the Weather Research and Forecasting ( WRF ) model with four‐dimensional data assimilation ( WRF‐FDDA ) to produce a high‐resolution climatography of seasonal precipitation over Israel and the surrounding areas. The system was used to dynamically downscale global Climate Forecast System ( CFS ) reanalysis with continuous assimilation of conventional and unconventional observations. Precipitation seasons (December‐January‐February) in 7 years, including two extreme dry and wet seasons observed in the past decades, were generated at 2‐km spatial resolution. Verification against rain‐gauge observations shows that the WRF‐FDDA system effectively reproduces the spatial and inter‐annual variability, as well as the timing, intensity, and length of wet and dry spells. The best agreement between model and observations was obtained at areas dominated by complex terrain, illustrating the benefit of the high‐resolution lower boundary forcing in the dynamical downscaling process. In contrast, some biases were observed over coastal‐flat terrain. The model was able to reproduce some of the extreme events, but exhibited limitations in the case of rare events. This specific discrepancy between the model and observations suggests that further fine tuning and different model configurations may be needed to correctly simulate extreme events. The use of an objective weather‐regimes verification procedure reveals the skill of the climatography for different types of extra‐tropical cyclones: while biases are larger at coastal‐flat areas under shallow‐cyclonic conditions, deep‐cyclonic conditions lead to more significant biases in complex terrain regions. The weather‐regimes dependent information may be used for further calibration of the downscaled precipitation.

Assessing the cost of living with elephants (Loxodonta africana) in areas adjacent to Meru National Park, Kenya - Anne J. Sitienei; Ge Jiwen; Shadrack M. Ngene (European Journal of Wildlife Research, 2014)

Molecular basis for insecticide‐enhanced thermotolerance in the brown planthopper N ilaparvata lugens S tål ( H emiptera: D elphacidae) - Lin‐Quan Ge; Liu‐Juan Huang; Guo‐Qin Yang; Qi‐Sheng Song; David Stanley; G. M. Gurr; Jin‐Cai Wu (Molecular Ecology, 2013)
Climate change is likely to have marked ecological effects on terrestrial ecosystems, including the activities of insect pests. Most attention has focused on the increasing geographical ranges of pests; however, if extrinsic factors enhance their thermotolerance, populations may express increased voltinism and longer daily and annual activity periods. These changes in pest populations have the potential for severe consequences, including increased crop losses and decreased food security at the global level. The brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) is a serious pest of rice crops in temperate and tropical regions of Asia. It is often present in rice microclimates at temperatures close to its maximum thermotolerance. Recent BPH outbreaks in tropical Asia are considered to be associated with excess use of pesticides and increasing temperature. This study tested whether exposure to sublethal concentrations of triazophos (tzp), an insecticide widely used in Asian rice production, enhances thermotolerance of BPH . Tzp exposure (40 ppm at 40 °C) significantly decreased mortality (from 94% in controls to 50% at 48 h post‐treatment) and increased lethal mean time ( LT 50 ) of adults by 17.2 h. To investigate the underlying molecular mechanism of this tzp‐enhanced thermotolerance, we selected Hsp70 and Arginine kinase (Argk) for detailed study. Transcripts encoding both proteins in third‐instar nymphs and brachypterous adult females were up‐regulated, compared with controls, after exposure to tzp. RNA i silencing of both genes demonstrated that Hsp70 and Argk are essential for survival and tzp‐increased thermotolerance. We propose that tzp induces thermotolerance in BPH s by increasing the expression of genes that act in cell protection mechanisms. The significance of our proposal relates to the importance of understanding the influence of sublethal concentrations of insecticides on pest biology. In addition to its influence on thermotolerance, tzp also enhances BPH reproduction. We infer that exposure to a pesticide stressor can produce cross‐tolerance, that is, increased tolerance to one stressor also increases tolerance to other stressors, including temperature. Aside from needing a better understanding of these effects in nature and in other pest/cropping systems, we suggest that pest management programmes can be improved with better understanding of the influences of stressors, including increased environmental temperatures and sublethal concentrations of insecticides, on pest biology.

In-depth proteomic analysis of human tropomyosin by top-down mass spectrometry - Ying Peng; Deyang Yu; Zachery Gregorich; Xin Chen; Andreas M. Beyer; David D. Gutterman; Ying Ge (Journal of Muscle Research and Cell Motility, 2013)

Expression profile of oestrogen receptors and oestrogen‐related receptors is organ specific and sex dependent: the Japanese medaka Oryzias latipes model - N. K. M. Cheung; A. C. K. Cheung; R. R. Ye; W. Ge; J. P. Giesy; D. W. T. Au (Journal of Fish Biology, 2013)
Gene expression of all known subtypes of oestrogen receptor ( ER ) and oestrogen‐related receptor ( ERR ) in multiple organs and both sexes of the Japanese medaka Oryzias latipes was profiled and systematically analysed. As revealed by statistical analyses and low‐dimensional projections, the expressions of ERRs proved to be organ and sex dependent, which is in contrast with the ubiquitous nature of ERs . Moreover, expressions of specific ERR isoforms ( ERRγ1 , ERRγ2 ) were strongly correlated with that of all ERs ( ERα , ERβ1 and ERβ2 ), suggesting the existence of potential interactions. Findings of this study shed light on the co‐regulatory role of particular ERRs in oestrogen‐ ERs signalling and highlight the potential importance of ERRs in determining organ and sex‐specific oestrogen responses. Using O. latipes as an alternative vertebrate model, this study provides new directions that call for collective efforts from the scientific community to unravel the mechanistic action of ER‐ERR cross‐talks, and their intertwining functions, in a cell and sex‐specific manner in vivo .

Laterality affects spontaneous recovery of contralateral hand motor function following motor cortex injury in rhesus monkeys - Warren G. Darling; Nicole Helle; Marc A. Pizzimenti; Diane L. Rotella; Stephanie M. Hynes; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Robert J. Morecraft (Experimental Brain Research, 2013)

Dynamic mobilization of PGC-1α mediates mitochondrial biogenesis for the protection of RGC-5 cells by resveratrol during serum deprivation - Shida Chen; Qian Fan; Ang Li; Dongjiang Liao; Jian Ge; Alan M. Laties; Xiulan Zhang (Apoptosis, 2013)

Doubled haploids of novel trigenomic Brassica derived from various interspecific crosses - X. X. Geng; S. Chen; I. A. Astarini; G. J. Yan; E. Tian; J. Meng; Z. Y. Li; X. H. Ge; M. N. Nelson; A. S. Mason; A. Pradhan; W. J. Zhou; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Field Measurement of P- and S-Wave Velocities for Wyoming Trona Deposit - M. Ge; H. Wang (Geotechnical and Geological Engineering, 2013)

High diversity and widespread occurrence of mitotic spore mats in ectomycorrhizal Pezizales - R. A. Healy; M. E. Smith; G. M. Bonito; D. H. Pfister; Z. ‐W. Ge; G. G. Guevara; G. Williams; K. Stafford; L. Kumar; T. Lee; C. Hobart; J. Trappe; et al. (Molecular Ecology, 2013)
Fungal mitospores may function as dispersal units and/ or spermatia and thus play a role in distribution and/or mating of species that produce them. Mitospore production in ectomycorrhizal (EcM) Pezizales is rarely reported, but here we document mitospore production by a high diversity of EcM Pezizales on three continents, in both hemispheres. We sequenced the internal transcribed spacer (ITS) and partial large subunit (LSU) nuclear rDNA from 292 spore mats (visible mitospore clumps) collected in Argentina, Chile, China, Mexico and the USA between 2009 and 2012. We collated spore mat ITS sequences with 105 fruit body and 47 EcM root sequences to generate operational taxonomic units (OTUs). Phylogenetic inferences were made through analyses of both molecular data sets. A total of 48 OTUs from spore mats represented six independent EcM Pezizales lineages and included truffles and cup fungi. Three clades of seven OTUs have no known meiospore stage. Mitospores failed to germinate on sterile media, or form ectomycorrhizas on Quercus, Pinus and Populus seedlings, consistent with a hypothesized role of spermatia. The broad geographic range, high frequency and phylogenetic diversity of spore mats produced by EcM Pezizales suggests that a mitospore stage is important for many species in this group in terms of mating, reproduction and/or dispersal.

Seasonal migration by a large forest ungulate: a study on takin (Budorcas taxicolor) in Sichuan Province, China - Tian-Pei Guan; Bao-Ming Ge; William J. McShea; Sheng Li; Yan-Ling Song; Chad M. Stewart (European Journal of Wildlife Research, 2013)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Identification and molecular characterisation of HMW glutenin subunit 1By16* in wild emmer - M. Jin; Z.-Z. Xie; P. Ge; J. Li; S.-S. Jiang; S. Subburaj; X.-H. Li; F.-J. Zeller; S.-L.-K. Hsam; Y.-M. Yan (Journal of Applied Genetics, 2012)

Effect of Assessment Scale on Spatial and Temporal Variations in CH4, CO2, and N2O Fluxes in a Forested Wetland - Zhaohua Dai; Carl C. Trettin; Changsheng Li; Harbin Li; Ge Sun; Devendra M. Amatya (Water, Air, & Soil Pollution, 2012)

Phylogenetic signals in the realized climate niches of Chinese grasses (Poaceae) - Qing Liu; Paul M. Peterson; Xue-jun Ge (Plant Ecology, 2011)

Analysis of phage Mu DNA transposition by whole-genome Escherichia coli tiling arrays reveals a complex relationship to distribution of target selection protein B, transcription and chromosome architectural elements - Jun Ge; Zheng Lou; Hong Cui; Lei Shang; Rasika M Harshey (Journal of Biosciences, 2011)

Protective effect of Gö6976, a PKD inhibitor, on LPS/d-GalN-induced acute liver injury in mice - G. J. Duan; J. Zhu; C. Y. Xu; J. Y. Wan; L. Zhang; X. D. Ge; L. M. Liu; Y. S. Liu (Inflammation Research, 2011)

Flow Residence Time and Regions of Intraluminal Thrombus Deposition in Intracranial Aneurysms - V. L. Rayz; L. Boussel; L. Ge; J. R. Leach; A. J. Martin; M. T. Lawton; C. McCulloch; D. Saloner (Annals of Biomedical Engineering, 2010)

Minimal forced use without constraint stimulates spontaneous use of the impaired upper extremity following motor cortex injury - Warren G. Darling; Marc A. Pizzimenti; Diane L. Rotella; Stephanie M. Hynes; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Tyler Vanadurongvan; David W. McNeal; Kathryn M. Solon-Cline; Robert J. Morecraft (Experimental Brain Research, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Modeling antibiotic resistance to project future rates: quinolone resistance in Escherichia coli - L. K. Durham; M. Ge; A. J. Cuccia; J. P. Quinn (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Carbon/nitrogen ratio as a major factor for predicting the effects of organic wastes on soil bacterial communities assessed by DNA-based molecular techniques - Yuan Ge; Chengrong Chen; Zhihong Xu; Simon M. Eldridge; Kwong Yin Chan; Yan He; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

Positive Allosteric Interaction of Structurally Diverse T-Type Calcium Channel Antagonists - Victor N. Uebele; Cindy E. Nuss; Steven V. Fox; Susan L. Garson; Razvan Cristescu; Scott M. Doran; Richard L. Kraus; Vincent P. Santarelli; Yuxing Li; James C. Barrow; Zhi-Qiang Yang; Kelly-Ann S. Schlegel; et al. (Cell Biochemistry and Biophysics, 2009)

Microseismic Monitoring at a Limestone Mine - M. Ge; M. Mrugala; A. T. Iannacchione (Geotechnical and Geological Engineering, 2009)

Isolation and identification of hydroxythiohomosildenafil in herbal dietary supplements sold as sexual performance enhancement products - L. Li; M.-Y. Low; F. Aliwarga; J. Teo; X.-W. Ge; Y. Zeng; B.C. Bloodworth; H.-L. Koh (Food Additives & Contaminants: Part A, 2009)

Resolution of GPS carrier-phase ambiguities in Precise Point Positioning (PPP) with daily observations - M. Ge; G. Gendt; M. Rothacher; C. Shi; J. Liu (Journal of Geodesy, 2008)

Resolution of GPS carrier-phase ambiguities in Precise Point Positioning (PPP) with daily observations - M. Ge; G. Gendt; M. Rothacher; C. Shi; J. Liu (Journal of Geodesy, 2008)

Settlement Characteristic of Beach Sands and Its Evaluation - T.-H. Kim; J.-M. Nam; L. Ge; K.-I. Lee (Marine Georesources & Geotechnology, 2008)

Velocity Distribution and Shear Rate Variability Resulting from Changes in the Impeller Location in the USP Dissolution Testing Apparatus II - Ge Bai; Piero M. Armenante (Pharmaceutical Research, 2008)

A proteomic approach for the identification of bismuth-binding proteins in Helicobacter pylori - Ruiguang Ge; Xuesong Sun; Qing Gu; Rory M. Watt; Julian A. Tanner; Benjamin Chun Yu Wong; Harry Huaxiang Xia; Jian-Dong Huang; Qing-Yu He; Hongzhe Sun (JBIC Journal of Biological Inorganic Chemistry, 2007)

A New Data Processing Strategy for Huge GNSS Global Networks - M. Ge; G. Gendt; G. Dick; F. P. Zhang; M. Rothacher (Journal of Geodesy, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Genetic differentiation and relationship of populations in the Aconitum delavayi complex (Ranunculaceae) and their taxonomic implications - F.-M. Zhang; W.-L. Chen; Q.-E. Yang; S. Ge (Plant Systematics and Evolution, 2005)

Improving carrier-phase ambiguity resolution in global GPS network solutions - M. Ge; G. Gendt; G. Dick; F. P. Zhang (Journal of Geodesy, 2005)

Strong genetic differentiation of the East-Himalayan Megacodon stylophorus (Gentianaceae) detected by Inter-Simple Sequence Repeats (ISSR) - X. -J. Ge; L. -B. Zhang; Y. -M. Yuan; G. Hao; T. -Y. Chiang (Biodiversity and Conservation, 2005)

Population structure of wild bananas, Musa balbisiana , in China determined by SSR fingerprinting and cpDNA PCR‐RFLP - X. J. GE; M. H. LIU; W. K. WANG; B. A. SCHAAL; T. Y. CHIANG (Molecular Ecology, 2005)
Both demographic history and dispersal mechanisms influence the apportionment of genetic diversity among plant populations across geographical regions. In this study, phylogeography and population structure of wild banana, Musa balbisiana , one of the progenitors of cultivated bananas and plantains in China were investigated by an analysis of genetic diversity of simple sequence repeat (SSR) fingerprint markers and cpDNA PCR‐RFLP. A chloroplast DNA (cpDNA) genealogy of 21 haplotypes identified two major clades, which correspond to two geographical regions separated by the Beijiang and Xijiang rivers, suggesting a history of vicariance. Significant genetic differentiation was detected among populations with cpDNA markers, a result consistent with limited seed dispersal in wild banana mediated by foraging of rodents. Nuclear SSR data also revealed significant geographical structuring in banana populations. In western China, however, there was no detected phylogeograpahical pattern, possibly due to frequent pollen flow via fruit bats. In contrast, populations east of the Beijiang River and the population of Hainan Island, where long‐range soaring pollinators are absent, are genetically distinct. Colonization–extinction processes may have influenced the evolution of Musa populations, which have a metapopulation structure and are connected by migrating individuals. Effective gene flow via pollen, estimated from the nuclear SSR data, is 3.65 times greater than gene flow via seed, estimated from cpDNA data. Chloroplast and nuclear DNAs provide different insights into phylogeographical patterns of wild banana populations and, taken together, can inform conservation practices.

Formation of wheat ( Triticum aestivum L.) embryogenic callus involves peroxide-generating germin-like oxalate oxidase - Mahmut Caliskan; Mge Turet; Andrew C. Cuming (Planta, 2004)

Virus Isolation for Diagnosing Dengue Virus Infections in Returning Travelers - D. Teichmann; K. Gbels; M. Niedrig; J.-W. Sim-Brandenburg; J. Lge-Stehr; M. P. Grobusch (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Viruses in subgroup 2 of the genus Ilarvirus share both serological relationships and characteristics at the molecular level - S. W. Scott; M. T. Zimmerman; X. Ge (Archives of Virology, 2003)

Herpes Simplex Virus-1 and Varicella-Zoster Virus Latency in Ganglia - Bradley M Mitchell; David C Bloom; Randall J Cohrs; Donald H Gilden; Peter GE Kennedy (Journal of NeuroVirology, 2003)

Identification of genome constitution of Oryza malampuzhaensis, O. minuta,and O. punctata by multicolor genomic in situ hybridization - C.-B. Li; D.-M. Zhang; S. Ge; B.-R. Lu; D.-Y. Hong (Theoretical and Applied Genetics, 2001)

Differentiation and inter-genomic relationships among C, E and D genomes in the Oryzaofficinalis complex (Poaceae) as revealed by multicolor genomic in situ hybridization - C.-B. Li; D.-M. Zhang; S. Ge; B.-R. Lu; D.-Y. Hong (Theoretical and Applied Genetics, 2001)

Omapatrilat in patients with hepatic cirrhosis - P. O'Grady; O. Vesterqvist; B. Malhotra; J. Manning; M. Jemal; G. Ge; B. Mangold (European Journal of Clinical Pharmacology, 2001)

Enhancement of protective immunity in blue gourami, Trichogaster trichopterus (Pallas), against Aeromonas hydrophila and Vibrio anguillarum by A. hydrophila major adhesin - H M Fang; K C Ling; R Ge; Y M Sin (Journal of Fish Diseases, 2000)
Blue gourami, Trichogaster trichopterus (Pallas), were intraperitoneally immunized with major adhesin, a 43 kDa OMP protein isolated from fish Aeromonas hydrophila , in the presence of Freund's complete adjuvant (FCA). Three weeks later, a booster injection of adhesin without FCA was administered. Control group fish were similarly treated with phosphate‐buffered saline (PBS) and FCA. Results showed that anti‐adhesin serum obtained from fish after booster immunization exhibited very strong ability in agglutinating bacterial cells. Although this antiserum had no bactericidal effect, it could significantly inhibit serologically different strains of A. hydrophila from invading EPC (Epithelioma papillosum of carp) cells in vitro . In addition, the proliferative response of head kidney leucocytes of these immune fish was significantly increased as compared to that of the control. The results also showed that the major adhesin could provide significant protective immunity to fish against the challenge by homologous and heterologous strains of A. hydrophila and one virulent strain of Vibrio anguillarum .

Reproductive biology and genetic diversity of a cryptoviviparous mangrove Aegiceras corniculatum (Myrsinaceae) using allozyme and intersimple sequence repeat (ISSR) analysis - X. J. Ge; M. Sun (Molecular Ecology, 1999)
Mangroves consist of a group of taxonomically diverse species representing about 20 families of angiosperms. However, little is known about their reproductive biology, genetic structure, and the ecological and genetic factors affecting this structure. Comparative studies of various mangrove species are needed to fill such gaps in our knowledge. The pollination biology, outcrossing rate, and genetic diversity of Aegiceras corniculatum were investigated in this study. Pollination experiments suggested that the species is predominantly pollinator‐dependent in fruit setting. A quantitative analysis of the mating system was performed using progeny arrays assayed for intersimple sequence repeat (ISSR) markers. The multilocus outcrossing rate ( t m ) was estimated to be 0.653 in a wild population. Both allozyme and ISSR were used to investigate genetic variation within and among populations. The combined effects of founder events and enhanced local gene flow through seedling dispersal by ocean currents apparently played an important role in shaping the population genetic structure in this mangrove species. Both allozyme variation ( P = 4.76%, A = 1.05, H E = 0.024) and ISSR diversity ( P = 16.18%, A = 1.061, H E = 0.039) were very low at the species level, in comparison with other woody plants with mixed‐mating or outcrossing systems. Gene differentiation among populations was also low: allozyme G ST = 0.106 and ISSR G ST = 0.178. The unusually high genetic identities (0.997 for allozyme and 0.992 for ISSR loci), however, suggest that these populations are probably all descended from a common ancestral population with low polymorphism.

A genetic linkage map of rat Chromosome 15 derived from five F 2 crosses - Jennifer S. Shepard; Elaine F. Remmers; Stephen Chen; Lisa Chang; Yutaka Kawahito; Pércio S. Gulko; Bina Joe; Ryan E. Longman; Svetlana Dracheva; Lynn Ge; Jianping Wang; Van R. Reese; et al. (Mammalian Genome, 1999)

Grid point search algorithm for fast integer ambiguity resolution - H. B. Iz; M. Ge; Y. Q. Chen (Journal of Geodesy, 1998)

Interaction of DNA-binding proteins with the 5′-flanking region of a cytokinin-responsive cucumber hydroxypyruvate reductase gene - Ge Jin; Maria C. Davey; John R. Ertl; Rui Chen; Zhu-tian Yu; Steven G. Daniel; Wayne M. Becker; Chong-maw Chen (Plant Molecular Biology, 1998)

A genetic linkage map of rat chromosome 20 derived from five F 2 crosses - Y. Kawahito; Elaine F. Remmers; R. L. Wilder; Ryan E. Longman; Pércio S. Gulko; Jianping Wang; Stephen Chen; Lisa Chang; V. R. Reese; Svetlana Dracheva; Lynn Ge; Jean H. Hoffman; et al. (Immunogenetics, 1998)

The sequence of RNA 1 and RNA 2 of tobacco streak virus: additional evidence for the inclusion of alfalfa mosaic virus in the genus Ilarvirus - S. W. Scott; M. T. Zimmerman; X. Ge (Archives of Virology, 1998)

The complete sequence of the genomic RNAs of spinach latent virus - X. Ge; S. W. Scott; M. T. Zimmerman (Archives of Virology, 1997)

Isolation and characterization of fish Aeromonas hydrophila adhesins important for in vitro epithelial cell invasion - S Y Lee; Z Yin; R Ge; Y M Sin (Journal of Fish Diseases, 1997)
The molecular mechanisms involved in the invasion of Aeromonas hydrophila (strain PPD 134/91) into host cells were studied in vitro using a carp epithelial cell line. Bacterial fractions were extracted with potassium thiocyanate (KSCN) to investigate the adhesins involved. Two groups of adhesins were found. The major group was high molecular weight proteins with the largest component being a 43‐kDa protein. Amino terminal sequence analysis indicated that this may have been an outer membrane porin. This supports previous suggestions that a 43‐kDa outer membrane protein may be important in adhesion of a human isolate of A. hydrophila . The minor group of adhesins were low molecular weight proteins likely to be less effective in mediating bacterial adhesion and invasion into carp epithelial cells.

Sublethal effects of ammonia in soft water on Atlantic salmon smolts at a low temperature - Sveinung Fivelstad; Harald Kallevik; Helge M. Iversen; Trond Mretr; Klement Vge; Martin Binde (Aquaculture International, 1993)